The shell-armoured trace fossil Ereipichnus pickerillensis from the Pliocene Moruga Formation, Trinidad: morphology and palaeoenvironment. Issue 3 (3rd July 2021) - Ali, Shaliza; Gingras, Murray; Wilson, Brent
Abstract: A new ichnospecies, Ereipichnus pickerillensis, is described from lower shoreface deposits of the Pliocene Casa Cruz Sandstone Member of the Moruga Formation on Trinidad. E. pickerillensis comprises horizontal and sub-horizontal tubular burrows that are lined with radially orientated, poorly imbricated bivalve and other small shell fragments. In the studied strata, E. pickerillensis is found in association with Zoophycos, Asterosoma, Thalassinoides, and other elements of the Cruziana ichnofacies.